Ajaran dan jalan kematian Syekh Siti Jenar - Mulkhan, Abdul Munir, 1946- (Yogyakarta : Kreasi Wacana, 2001)
On the sufism teachings and death of Syekh Siti Jenar, one of the Wali Songo.
Includes bibliographical references.
Keywords: Mysticism -- Islam -- Indonesia -- Java